The Future Engineer - A labor market study based on the Global Systems Master of Science in Engineering Program - Häger, Anders; Qvirist, Edvin (My University, 2020)
This thesis studies the labor market for the new program Global Systems at Chalmers University of Technology that will begin fall 2020. Global Systems is a masters of science in engineering program in systems engineering with an interdisciplinary perspective. The study was conducted through semi-structured interviews with potential employers of the Global Systems engineer located in the Gothenburg area. Various work roles and competences required for the Global Systems engineer was suggested and discussed such as project experience and problem solving competence. It was found that organizations especially expect engineers to learn more communication and cooperation in future educations than they do today. There also seemed to be a positive perspective towards educating systems engineers as a wide range of organizations could use this type of specialization. Transcriptions of interviews conducted are presented in appendix.
Keywords: Chalmers University of Technology; Global Systems; systems engineering labor market